ANALISIS KELAYAKAN PENGEMBANGAN USAHA JAMUR TIRAM PUTIH “RUMAH JAMUR NANDO” DI PEKANBARU - Sri Indrastuti; Hamdi Agustin; Tuti Wulandari (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Nando mushroom house is not only a place for oyster mushroom cultivation, but also as a tourist and educational place about white oyster mushroom cultivation to attract visitors. The purpose of this study was to analyze the financial feasibility of the white oyster mushroom business at Rumah Mushroom Nando in Sialang Sakti Village, Tenayan Raya District, Pekanbaru City, Riau Province which includes: benefits, costs, investment criteria (Gold Value Method (GVM), Gold Index (GI), Net Present Value (NPV), Internal Rate of Return (IRR), NET B/C, Payback Period (PP). Based on the calculation results of GVM, GI, NPV, IRR, Net B/C Ratio and Payback Period, it shows that all calculation results in the category are feasible to be developed. Thus the White Oyster Mushroom Business